Magnetic Properties of LnIII–CuII 15‐Metallacrown‐5 Dimers with Terephthalate (LnIII = Pr, Nd, Sm, Eu). Issue 30 (10th August 2018) - Pavlishchuk, Anna V.; Kolotilov, Sergey V.; Zeller, Matthias; Lofland, Samuel E.; Addison, Anthony W.
Abstract : Metathesis of the isomorphous 15‐metallacrown‐5 complexes {[LnCu5 (GlyHA)5 (SO4 )(H2 O)6.5 ]}2 (SO4 )· 6H2 O (Ln III = Pr, Nd, Sm, Eu; GlyHA 2– = glycinehydroxamate) with excess p ‐bdc 2– ( p ‐bdc 2– = terephthalate) gave pairs of isomorphous complexes {[LnCu5 (GlyHA)5 (CO3 )(H2 O)4 ]2 ( p ‐bdc)}· 15H2 O [Ln = Pr (1 ) and Nd (2 )] and {[LnCu5 (GlyHA)5 (SO4 )(H2 O) x ]2 ( p ‐bdc)}· y H2 O [Sm (3 ) x = 5, y = 12; Eu (4 ), x = 4, y = 14] as outcomes of partial sulfate replacement. Complexes1 –4 are discrete dimers with two 15‐metallacrown‐5 blocks LnCu5 3+, a bridging p ‐bdc 2– and a bidentate capping anion on each Ln 3+ . The anion caps in1 and2 are carbonates from atmospheric CO2 capture, while in3 and4 the anion caps are sulfates. Between 3 K and 300 K, intrametallacycle antiferromagnetic exchange interactions amongst the Cu 2+ dominate the magnetic properties of1 –4, while for the Ln 3+, spin‐orbit coupling and crystal field effects are significant, the former being greater for Sm 3+ and Eu 3+ . The experimental χM T vs. T data were fitted with an additive model reflecting the dominance of the Cu··· Cu superexchange, while Ln 3+ ··· Cu 2+ exchange interactions were taken into account through a molecular field approach. The best‐fit values (–2 JCu–Cu ) for the intercopper superexchange interactions range from 88 to 120 cm –1 ; the g ‐factors, spin‐orbit coupling ( λ ) and axial crystal field splitting (Δ) parameter values are typical for Ln III . Abstract : Structural and magnetic studies of two pairs of discrete isomorphous 15‐MC‐5 dimers containing LnCu5 3+ units (Ln = Pr, Nd, Sm, Eu) bridged by terephthalates were performed. The χM T vs. T data obtained were fitted with an additive model, which considers exchange interactions JCu–Cu in the LnCu5 3+ units to be dominant. All possible weak exchange interactions were included with a molecular field approach.